APLIKASI KEGIATAN RIYADHAH DALAM MEMBENTUK AKHLAK SANTRI (Studi Kasus di MA Pancasila Kota Bengkulu) - Koesmeiran, Hengki; Kasmantoni; Utami, Intan (JPT : Jurnal Pendidikan Tematik, 2022)
Moral decadence does not only hit government officials, but also teenagers who will become the successors of the nation's struggle. In handling morals or morals it takes a long time that is sustainable and is istiqomah in guiding students. One effort that can be made to change a person's character is through the application of riyadhah which is used as a center for changing bad behavior to be directed into good behavior. As applied in the Pancasila Islamic Boarding School, namely dhikr and fasting. The formulation of the problem in this study is how the application of riyadhah activities in shaping the morals of students and what are the obstacles in the application of riyadhah activities. This study aims to describe the application of riyadhah activities in shaping the morals of students. This type of research is descriptive qualitative, as the primary data are the administrators and students of the Pancasila Islamic Boarding School in Bengkulu City and the secondary data are the results of interviews, literature, books, and other literature. Data collection techniques using observation techniques, interviews and documentation. The results of the research from observations and interviews that the application of riyadhah activities in shaping the morals of students through riyadhah dhikr and fasting activities have been applied properly and in accordance with applicable rules.